2018
DOI: 10.1177/0363546518781338
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Upper Extremity Injuries in NCAA Men’s and Women’s Ice Hockey

Abstract: Men and women sustained a significant number of UE injuries playing collegiate ice hockey during the period studied, with acromioclavicular joint sprain being the most common UE injury and the one that most frequently led to significant time loss. These data may provide insight for future injury prevention and guide improvements in training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 15 publications
3
45
1
1
Order By: Relevance
“…A peak for dislocations was observed in the twenties; whereas, the incidence was similar from the teens until 60 years of age for sprains. These observations support the findings of other studies describing a majority of young men in sports with ACJ injuries [23,24,27,28]. Men with acute Rockwood types III-VI do also have more associated articular lesions [33].…”
Section: Discussionsupporting
confidence: 90%
“…A peak for dislocations was observed in the twenties; whereas, the incidence was similar from the teens until 60 years of age for sprains. These observations support the findings of other studies describing a majority of young men in sports with ACJ injuries [23,24,27,28]. Men with acute Rockwood types III-VI do also have more associated articular lesions [33].…”
Section: Discussionsupporting
confidence: 90%
“…34 Melvin et al found that shoulder dislocations and subluxations ranked among the most common causes of time lost (time loss !14 days) from sport among collegiate hockey players. 29 Okoroha et al found that 92.8% of athletes were able to RTP after a shoulder instability event in a study of the National Football League (NFL) between 2006 and 2014, independent of treatment modality. However, those who underwent operative treatment returned after 39.3 weeks, whereas conservatively managed athletes returned after 2.3 weeks (P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…The AC joint is the most commonly injured shoulder structure in ice hockey players, and AC joint sprains or dislocations are the common shoulder injuries in National Collegiate Athletic Association ice hockey players. 25 The Figure 1. Overview of clavicle anatomy and classification systems by area of injury.…”
Section: Acromioclavicular Jointmentioning
confidence: 99%
“…The AC joint is the most commonly injured shoulder structure in ice hockey players, and AC joint sprains or dislocations are the common shoulder injuries in National Collegiate Athletic Association ice hockey players. 25 The mechanism of injury is typically by direct contact of the shoulder with another player or an apparatus, such as the boards or glass surrounding the ice surface, which drives the acromion inferiorly, causing a sprain or tear in the AC and/or coracoclavicular (CC) ligaments. AC joint injuries are categorized according to the Rockwood classification ( Table 1 ), which helps guide management of these injuries.…”
Section: Acromioclavicular Jointmentioning
confidence: 99%
See 1 more Smart Citation